EVALUASI PENGENDALIAN INTERNAL TERHADAP DANA KAS KECIL PADA KANTOR CABANG PT. SURYA MAS AGUNG - Mulia Rahmah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
One important aspect of a company is the system of internal control. Internal control system are policies and procedures that protect assets from misuse and embezzlement and irregularities. The purpose of this study was to evaluate the role of internal control petty cash fund applied Branch Office PT. Surya Mas Agung. From research conducted then known to have had elements of internal control as an organizational structure that strictly separates responsibility, the system of authorization and recording procedures, and practice healthy in payment details to avoid misuse and misappropriation From the above results indicate that Branch Office PT. Surya Mas Agung has met the elements of internal control.